Crafting Engineers for Tomorrow: Aligning Education with Industry to Achieve Sustainable Development - Aryani Widyakusuma; Reza Rachman Hakim (Pusat Publikasi Nusantara, 2024)
This study addresses the critical gap between engineering education and industry demands, focusing on the integration of Industry 4.0 technologies and experience-based learning frameworks such as the MBKM program in Indonesia. By emphasizing practical skills, project management, and soft skills, this research explores how academic institutions can better prepare students for the challenges of a rapidly evolving, AI-driven workplace while contributing to Sustainable Development Goals. Using a descriptive methodology that combines case studies and literature reviews, the study evaluates the impact of industry collaboration, experiential learning, and curriculum alignment on workforce readiness and graduate employability. Findings highlight the importance of fostering adaptability, innovation, and sustainability in engineering education, ensuring that graduates are equipped to lead and thrive in dynamic professional environments. The study concludes with actionable recommendations for enhancing academia-industry partnerships, embedding lifelong learning, and advancing sustainability principles in engineering curricula, paving the way for a more robust and globally competitive workforce.